The Effect of Tactor Composition and Vibrotactile Stimulation on Sensory Memory for a Haptic Feedback Display - Kelly, Erin; Wheaton, Lewis A.; Hammond, Frank L. (IEEE RO-MAN, 2023)
Previously, a wearable multimodal sensory feedback device (SFD) was developed to communicate proprioceptive information from a robotic gripper onto the operator's forearm. The SFD showed promise in that it could effectively communicate proprioceptive sensory information and enhance the body's natural proprioceptive sense. This study delves into the feedback modes implemented into the feedback device by evaluating the effect that increased skin-stretch in combination with vibrotactile stimulation has on the users' abilities to discern the location of the tactor after time has passed. The SFD used in this study implements a tactor, made of either silicone or foam that translates laterally across the ventral side of the forearm. Subjects were asked to sense the location of the tactor after it had been stationary for a period of time. The experiments' results indicate that a material that provides increased skin-stretch sensation can benefit the duration of skin-stretch feedback for sensory feedback devices. Additionally, vibrotactile stimulation has shown to be promising though its compatibility with the silicone material was not ideal.